2009
DOI: 10.1183/09031936.00074909
|View full text |Cite
|
Sign up to set email alerts
|

EIA and GC/MS analysis of 8-isoprostane in EBC of children with problematic asthma

Abstract: Asthmatic airways are characterised by enhanced oxidative stress, which can be studied by measuring biomarkers, such as 8-isoprostane. The aims of the present study were: 1) to measure the concentrations of 8-isoprostane in exhaled breath condensate (EBC) and urine of children with problematic and well-controlled asthma; 2) to compare the concentrations of 8-isoprostane measured by gas chromatographic/negative ion chemical ionisation mass spectrometry (GC/NICI-MS) and by an enzymatic immunoassay (EIA).We recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…The lowest detection limit was 3.7 pg?mL -1 . For samples below the lowest detection limit, data were arbitrarily expressed as half the detection limit [23]. This assay was previously validated using a reference analytical method (gas chromatographic/negative ion chemical ionisation mass spectrometry) [23].…”
Section: Population and Study Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The lowest detection limit was 3.7 pg?mL -1 . For samples below the lowest detection limit, data were arbitrarily expressed as half the detection limit [23]. This assay was previously validated using a reference analytical method (gas chromatographic/negative ion chemical ionisation mass spectrometry) [23].…”
Section: Population and Study Designmentioning
confidence: 99%
“…For samples below the lowest detection limit, data were arbitrarily expressed as half the detection limit [23]. This assay was previously validated using a reference analytical method (gas chromatographic/negative ion chemical ionisation mass spectrometry) [23]. The repeatability of the EIA 8-isoprostane measurements in EBC on two different days had previously been tested at our laboratory, showing a coefficient of repeatability of 3.2 pg?mL -1 .…”
Section: Population and Study Designmentioning
confidence: 99%
“…Leukotriene B 4 , prostaglandin E2 and 8-isoprostane in breath condensate from the nose and the mouth were analysed in an attempt to study the relationship between persistent allergic rhinitis and asthma; possible correlations were reported [94]. In two other paediatric studies, eoxin and eotaxin were measured in EBC along with 8-isoprostane, all three were significantly increased in children with problematic severe asthma [95,96]. Finally, a new and advanced approach to utilising EBC was reported by BLOEMEN et al [97].…”
Section: Biomarkers In Bal and Sputummentioning
confidence: 99%
“…Few, if any, EBC biomarkers have been validated for clinical use, and considerable methodological challenges remain [74]. A recent study [75] demonstrated an increased level of EBC 8-isoprostane in children with problematic asthma suggesting a role for oxidative stress in this asthma phenotype.…”
Section: Exhaled Breath Condensatementioning
confidence: 99%